2018
DOI: 10.1016/j.jinorgbio.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

The role of Ala134 in controlling substrate binding and reactivity in ascorbate peroxidase

Abstract: Ascorbate peroxidase (APX) is a class I heme peroxidase. It has two sites for binding of substrates. One is close to the γ-heme edge and is used for oxidation of ascorbate; the other is at the δ-heme edge and is used for binding of aromatic substrates [Gumiero et al., (2010) Arch. Biochem. Biophys. 500, 13-20]. In this work, we have examined the structural factors that control binding at the δ-heme edge by replacement of Ala134 in APX with a proline residue that is more commonly found in other class II and III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Yang et al [ 86 ] reported an upregulation of HSP 70 in Phaeodactylum tricornutum under N stress. Ascorbate peroxidase (APX) exists in isoforms in different subcellular organelles such as peroxisome, chloroplasts, cytosol, and mitochondria and helps plants detoxify H 2 O 2 by converting it into H 2 O [ 87 , 88 ]. Chaperonin 60 kDa protein (Spot 29), was upregulated in PP2C9TL under low N, these chaperonins which help and guide cells in the correct folding of proteins both in normal conditions [ 89 ] and under stress [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [ 86 ] reported an upregulation of HSP 70 in Phaeodactylum tricornutum under N stress. Ascorbate peroxidase (APX) exists in isoforms in different subcellular organelles such as peroxisome, chloroplasts, cytosol, and mitochondria and helps plants detoxify H 2 O 2 by converting it into H 2 O [ 87 , 88 ]. Chaperonin 60 kDa protein (Spot 29), was upregulated in PP2C9TL under low N, these chaperonins which help and guide cells in the correct folding of proteins both in normal conditions [ 89 ] and under stress [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…the corresponding position that may promote a higher tolerance against inactivation by H 2 O 2 and/or enhancing oxidation of phenolic substrates (110,111). Yet, despite the improvements made to the enzyme, APEX2 remains less active than HRP and more sensitive to H 2 O 2 mediated inhibition (110), suggesting that further improvements may be possible.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Last but not least, proteomics has been employed to analyze the proteome of seeds and changes associated to seed maturation and germination in an attempt to characterize and differentiate, at the molecular level, orthodox and non-orthodox species and zygotic and somatic embryos ( [18,19,[86][87][88][89][90][91][92][93]; this study is of great importance for propagation and seed conservation programs.…”
Section: Development: Seed Maturation and Germinationmentioning
confidence: 99%
“…Terpenes constitute a large class of secondary metabolites that serve multiple roles in the interactions between plants and their environment, including biotic and abiotic stress responses [88]. They are involved in environmental stimuli perception, stress, and phytohormone signaling [89,90].…”
Section: Proteins Related To 'Response To Stimuli' Under Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation